When do bursts matter in the primary motor cortex? Investigating changes in the intermittencies of beta rhythms associated with movement states. (February 2023) - West, Timothy O.; Duchet, Benoit; Farmer, Simon F.; Friston, Karl J.; Cagnan, Hayriye
Abstract: Brain activity exhibits significant temporal structure that is not well captured in the power spectrum. Recently, attention has shifted to characterising the properties of intermittencies in rhythmic neural activity (i.e. bursts), yet the mechanisms that regulate them are unknown. Here, we present evidence from electrocorticography recordings made over the motor cortex to show that the statistics of bursts, such as duration or amplitude, in the beta frequency (14–30 Hz) band, significantly aid the classification of motor states such as rest, movement preparation, execution, and imagery. These features reflect nonlinearities not detectable in the power spectrum, with states increasing in nonlinearity from movement execution to preparation to rest. Further, we show using a computational model of the cortical microcircuit, constrained to account for burst features, that modulations of laminar specific inhibitory interneurons are responsible for the temporal organisation of activity. Finally, we show that the temporal characteristics of spontaneous activity can be used to infer the balance of cortical integration between incoming sensory information and endogenous activity. Critically, we contribute to the understanding of how transient brain rhythms may underwrite cortical processing, which in turn, could inform novel approaches for brain state classification, and modulation with novel brain-computer interfaces. Highlights: Properties of beta band (14-30 Hz) bursts recorded in electrocorticography are altered across motor states such as preparation and execution. These transient events represent significant properties of neural signals, independent to that measured in spectral power. A computational model of the cortical motor circuit suggests that bursts properties are shaped by layer specific interneuron inhibition. This model shows that the properties of spontaneous burst activity can predict the propagation and gating of sensory inputs to the cortex.